A HOLISTIC INQUIRY INTO RISK COMMUNICATION DYNAMICS: YOUTH-LED INITIATIVES AND SOCIETAL ENGAGEMENT IN SURABAYA'S RURAL LANDSCAPES - Ida, Rachmah; Kinasih, Sri Endah; Febriyanti, Syafrida Nurrachmi; Puspa, Ratih; Romadhona, Mochamad Kevin (Universitas Padjadjaran, 2024)
The overarching aim of this community service program is to contribute significantly to the understanding of risk communication dynamics and its profound implications within broader societal contexts. Beyond mere dissemination of information, this initiative serves as a comprehensive study, delving into the intricate web of societal attitudes, perceptions, and the intricate pathways through which information traverses within communities. Central to this endeavor is the creation of educational videos geared towards enhancing community awareness, particularly targeting the youth in rural village settings. These videos, crafted by local youth in Surabaya, encapsulate not only informative content but also culturally nuanced messaging that resonates deeply with the intended audience. Methodologically, the program adopts a multifaceted approach. Firstly, it involves the online dissemination of educational materials, strategically targeting bustling areas in Surabaya, notably Petemon and Kaliasin. Secondly, it encompasses Focus Group Discussions with children, providing invaluable insights into their utilization of smartphone cameras and their perceptions of media content. Lastly, the program includes a hands-on video workshop, empowering children to actively participate in the creation of visual narratives, thereby fostering a sense of ownership and agency. The duration of the research spanned a comprehensive 15-day period, allowing for in-depth exploration and analysis of community dynamics and perceptions. The outcomes of these community engagement activities unveil nuanced layers of perception and understanding regarding COVID-19 prevention programs, particularly the government's vaccination efforts. Notably, there emerges a preference for peer-driven engagement, with individuals opting to involve those within their immediate social circles. Within this communal framework, the created videos serve as powerful tools, employing a blend of straightforward visual storytelling and everyday language to effectively communicate crucial messages, thereby fostering a sense of collective responsibility and empowerment within the community.